2010
DOI: 10.3109/13697131003660585
|View full text |Cite
|
Sign up to set email alerts
|

Long-term endometrial and breast safety of a specific, standardized soy extract

Abstract: As no case of hyperplasia was diagnosed among the 301 interpretable biopsies at 1 year and there was only one case of simple hyperplasia in the 197 post-baseline biopsies at 3 years, the endometrial safety of this extract has been demonstrated. Furthermore, as demonstrated by the lack of change in endometrial thickness associated with the histologic results, we suggest that this extract does not exert a mitogenic effect on the endometrium. These results suggest that daily administration of 70 mg of a specific,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 34 publications
1
14
0
1
Order By: Relevance
“…Indeed, soy isoflavone tablets easily allow intake in excess of 100 mg isoflavones/d, five times that of isoflavone intake from typical Asian diets 1 . One long-term (3 y) study 2 indicated that soy isoflavone (extract form) intake was safe for the endometrium and breast, another (2 y) study 3 demonstrated that soy hypocotyl isoflavones (80 or 120 mg) did not adversely affect endometrial thickness, and another recent (1 y) study 4 showed that soy isoflavones (60 mg) combined with Lactobacillus sporogenes was safe for the endometrium, mammary glands, and liver function. Indeed, a 2-y study 5 indicated that genistein (54 mg/d), the predominant soybean isoflavone, reduced the mean number of hot flushes/d, but it did not affect the endometrium.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, soy isoflavone tablets easily allow intake in excess of 100 mg isoflavones/d, five times that of isoflavone intake from typical Asian diets 1 . One long-term (3 y) study 2 indicated that soy isoflavone (extract form) intake was safe for the endometrium and breast, another (2 y) study 3 demonstrated that soy hypocotyl isoflavones (80 or 120 mg) did not adversely affect endometrial thickness, and another recent (1 y) study 4 showed that soy isoflavones (60 mg) combined with Lactobacillus sporogenes was safe for the endometrium, mammary glands, and liver function. Indeed, a 2-y study 5 indicated that genistein (54 mg/d), the predominant soybean isoflavone, reduced the mean number of hot flushes/d, but it did not affect the endometrium.…”
Section: Introductionmentioning
confidence: 99%
“…Also, it has been shown that the proportions of the more active free isoflavones in the circulation were markedly higher (20-150 times) in rodents than in humans (Setchell et al, 2011). Furthermore, over the past few years human studies have not confirmed the adverse effects found in in vitro and in animal studies, except for a disputable adverse effect related to endometrial thickness (Unfer et al, 2004), which was not confirmed in more recent studies (Alekel et al, 2014;D'Anna et al, 2007;Palacios et al, 2007;Palacios et al, 2010).…”
Section: Introductionmentioning
confidence: 59%
“…In two studies (Palacios 2010 andColacurci 2013) endometrial and breast safety aspects were the primary endpoint. Khan (2012) specifically investigated breast epithelial cell proliferation, which was presumed to be beneficially influenced by isoflavones.…”
Section: Results Objective 1: Human Studiesmentioning
confidence: 99%
“…No studies were specifically powered for adverse effects on thyroid, endometrium or breast. The study by Colacurci et al (2013) did not report a sample size calculation; the study by Palacios et al (2010) was a prospective open-label study, without control group. This means that it's unclear whether there is sufficient power to detect a difference should there be one.…”
Section: 2mentioning
confidence: 99%